Study Of The Aesthetic Form Of Wood Craft Furniture Design By Barata Sena - Triyanti, Triyanti; Karju, Karju (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2023)
This study focuses on five woodcraft furniture designs by Barata Sena that have been exhibited, namely the Groovy Grey Dining Table, Selendang Console Table, Coffee Table Soft Miami Blue, Wall Panel, and Cabinet Bontos Effect with 4 Drawer. The analysis of the aesthetic form of these five woodcraft furniture designs by Barata Sena is conducted using an interpretative analysis method with an approach to furniture aesthetics. The interpretation analysis is intended to examine Barata Sena's woodcraft furniture designs. Aesthetics in a furniture design can be observed through its composition of principles. Aesthetic form, emotionally, aims to present symbolic images for enthusiasts or users. The forms of the five Barata Sena furniture designs as a whole tend to be in the realm of Geometric Abstraction. These Barata Sena furniture designs not only have geometric basic shapes but are also configured with organic forms. The crafting techniques and finishing applied by Barata Sena tend to be innovative, which is the result of a fairly extensive exploration in order to achieve textures, colors, and constructions with appealing freshness.